Mapeamento do fenômeno da nominalização deverbal no discurso de popularização da ciência na revista Veja on-line - Adames, Fátima Andréia de Jesus Tamanini (2016)
The concepts of text, discursive practice and social practice of the Critical Discourse Analysis (CDA) are connected to the notions of recontextualization and interdiscursivity. In the discursive, social and ideological practice of popularization of Science (PC), the academic discourse is recontextualized in the journalistic discourse. Both PC genres and academic genres participate in the circulation of the knowledge and are part of a same genre system "that (re)creates and maintains Science" (MOTTA-ROTH; SCHERER, 2012). One way to verify the interdiscursivity between these genres is the identification of the deverbal nominalization (NDV), a brand of the science discourse. The NDV is a type of experiential grammatical metaphor (HALLIDAY; MATTHIESSEN, 2004) and as such works as an index of abstraction (FAIRCLOUGH, 2003). Listeners and readers lose part of the information on this type of nominalization, which requires an exercise in abstraction. Therefore, this thesis aims to map the NDV phenomenon as a discursive constitution of the process of science recontextualization. The interdiscursivity is the analytic category lexically and grammatically mapped through the linguistic exponent of the NDV in news which recontextualize different knowledge areas in Brazilian journalistic media. The results show that identifying the density of NDV in PC discourse is one way to identify how journalistic media recontextualizes the ideational content of Science: if in the direction of a discourse more abstract and more objective, or if in the direction of a discourse less abstract and more subjective. The analysis of the nominalization as experiential grammatical metaphor in the context of PC, therefore, collaborates on characterization of genres and registers (GOUVEIA, 2012) involved in the system of genres that participate in the circulation of knowledge.